Asignación presupuestaria y su relación con la ejecución de gasto del programa nacional de alimentación escolar Qali Warma región Loreto periodo 2018 – 2023 - Valverde Marin, Carla Cate (2025)
Social programs involve the organized execution of strategies aimed at the most vulnerable sectors, with the purpose of ensuring an equitable distribution of economic resources and improving the quality of life of the population. For this reason, the purpose of this research is to identify the relationship between budget allocation and expenditure execution in said program, focused on the Loreto region and to include a period of six years. Using a quantitative approach, with a non-experimental design and correlational level, the study analyzes the financial records of QALI WARMA to understand the coherence between the allocated resources and their effective execution. The results of the study reveal a perfect and statistically significant assessment between the budget allocation and expenditure execution of the QALI WARMA program in the Loreto region during the period 2018-2023, with a Pearson assessment coefficient of 1.000 and a significance of 0.000. In particular, regular resources accounted for the majority of funding, consolidating as the main source and showing an annual growth trend that reflects the commitment to sustain and strengthen the program. Despite a decline observed in 2020, likely related to the COVID-19 pandemic, both allocation and expenditure execution resumed an upward trend in subsequent years, peaking in 2023. These results suggest an adaptive response by the program’s financial management to fluctuations and highlight the importance of regular resources in ensuring the continuity and effectiveness of QALI WARMA in the region.